The Efficiency of Eastern Mediterranean University: Evidence from a Data Envelopment Analysis - Tegha, Vitalis Nkeng (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Academic works have been carried out to measure the productivity and performance of many Universities around the world. Most of these studies are done in accounting terms but the main challenge of industries today is how well work is being done in this organizations. This leads us to the topic of this thesis organizational efficiency. Talking about efficiency, most writing on this subject have focused on comparing efficiency among organizations or department within an organization. But in this work we will be measuring the efficiency of an organization. The main motivation for this thesis is to measure the concept of efficiency and productivity of Eastern Mediterranean University over the year between 1990 and 2015 by conducting Data Envelopment Analysis (DEA) efficiency scores and Malmquist Productivity Index. This work focuses on non-parametric measurement of efficiency to determine the efficiency of Eastern Mediterranean University (EMU). The result shows that most of the years are efficient and productive (all efficiency scores are close to 1 or equal to 1) in terms of technical efficiency and productivity. Keywords: EMU, DEA, Malmquist index, number of staff, number of graduated students

Öz: Yapılan birçok akademik çalışma, etkinlik ve verimlilik konsptinin diğer kurumlarda olduğu gibi üniversitelerde de önemli olduğu vurgulanmaktadır. Çalışmaların çoğu örgüsel bağlamda olduğu için örgüt içerisinde yapılacak performansında önemi çok büyüktür. Bu durum örgütsel verimliliğin önemini işaret ediyor olmasına rağmen, örgüt içi verimlilik ve etkinlik çok daha fazla ehemiyet taşımaktadır. Bu tezin ana motivasyonun amacı Doğu Akdeniz Üniversitesinin 1990 ile 2015 yılları arasındaki etkinliği ve verimliliği ölçülmesidir. Bu çalışmada Veri Zarflama metodu ile Malmquist index metodu kullanılmıştır. Çalışmanın sonuçları birçok yılın teknik etkinlik ve üretkenlik bağlamında olumlu olduğunu açıklamaktadır. Anahtar kelimeler: Doğu Akdeniz Üniversitesi, Veri Zarflama Metodu Malmquist index metodu, çalışan personel sayısı, mezun olan öğrenci sayısı
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2016. Supervisor: Prof. Dr. Sami Fethi.
Keywords: Business Administration; Marketing Management; Organizational Efficiency; Measurement; Eastern Mediterranean University; EMU; DEA; Malmquist index; number of staff; number of graduated students